Risk and risk factors for revision after primary reverse shoulder arthroplasty for cuff tear arthropathy and osteoarthritis: a Nordic Arthroplasty Register Association study - Lehtimäki, Kaisa; Rasmussen, Jeppe V.; Mokka, Jari; Salomonsson, Björn; Hole, Randi; Jensen, Steen Lund; Äärimaa, Ville (Journal of shoulder and elbow surgery, 2018)
Reverse shoulder arthroplasty (RSA) has gained increasing popularity in the treatment of rotator cuff tear arthropathy (CTA). The purpose of this study was to evaluate the survival of RSA and the risk factors for revision following RSA. RSA patients with CTA or osteoarthritis were identified from the Nordic Arthroplasty Register Association registry data (2004-2013). Kaplan-Meier survival analysis was used to calculate survival probabilities. Cox multiple regression analysis was used to calculate revision rates adjusted for sex, arthroplasty brand, age (<70 years), and year of surgery. The study included 1904 patients with RSA (1904 RSAs) (69% women; mean age, 74 years; age range, 35-97 years). Revision was performed in 95 patients (5%), with a 10-year cumulative revision rate of 0.91. The most common reason for revision was infection (n = 42), followed by loosening (n = 16) and instability (n = 12). Most revisions occurred less than 6 months after the primary operation. Men had a significantly increased risk of revision compared with women (risk ratio, 3.8; 95% confidence interval, 2.4-6.1). The most common implants were the Delta Xtend (n = 1366) and Delta Mark III (n = 246). The risk of revision of the Delta Mark III was 2.1 (95% confidence interval, 1.1-4.3) compared with the Delta Xtend. Age and year of surgery were not statistically significantly associated with risk of revision. The overall midterm risk of revision after RSA for CTA was low (5%). The most common reason for early revision was infection. Male sex was associated with a significantly increased risk of revision.